Lack of association between ABCB1 and ABCC2 gene polymorphisms and drug-resistant epilepsy in Peruvian patients. - Calderón-Toledo, Susana (2019)
Variants of the genes ABCB1 and ABCC2 have been associated with an increased risk of drug-resistant epilepsy; this phenomenon, however, has been scarcely tested by means of comparisons between populations: In Latin America there have only been 3 studies. Objective: To evaluate the association between the variants C3435T of the gene ABCB1, and --24C> T of the gene ABCC2 with drug-resistant epilepsy in Peruvian patients treated at the Epilepsy Unit of a Peruvian Hospital. Material and Methods: Blood samples from 22 patients with drug-resistant epilepsy and eight patients with pharmaco-responsive epilepsy were analyzed between May 2016 and June 2017. The identification of the C3435T variant of the ABCB1 gene was performed by polymerase chain reaction (PCR) and subsequent enzymatic digestion; the -24C>T variant of the ABCC2 gene was obtained by sequencing. Results: An allelic frequency of 0.717 was obtained for C in the C3435T variant of the gene ABCB1, and 0.967 for C in the -24C> T variant of the gene ABCC2. When genetic and allelic frequencies were compared between drug-resistant and drug-responsive patients no significant difference was observed, from which a lack of association between drug-resistant epilepsy and the C3435T variant of the gene ABCB1 and the -24C> T variant of the gene ABCC2 (p> 0.05) was inferred. Conclusions: In a sample of Peruvian patients with epilepsy, no association was found between drug-resistant epilepsy and the C3435T and -24C>T polymorphisms of the genes ABCB1 and ABCC2, respectively.